THE ROLE OF SOCIAL MEDIA USAGE AND WORK-LIFE BALANCE IN ENHANCING EMPLOYEE PERFORMANCE IN GOVERNMENT AGENCIES - Irsan Febriansyah (RADJA PUBLIKA, 2026)
This study aims to examine the influence of social media usage and work-life balance on employee performance at the Regional Office of the Directorate General of Customs and Excise of Eastern Sumatra. This study employed a quantitative method with an objective, measurable approach, using numerical data to analyze the relationship between research variables. The data used consisted of primary data obtained through questionnaires and secondary data obtained from related reports. The sample in this study comprised all 100 employees of the Regional Office of the Directorate General of Customs and Excise of Eastern Sumatra, using saturated sampling. The data analysis technique used was multiple linear regression to examine the influence of social media usage and work-life balance on employee performance. The results of the study indicate that social media use focused on professional goals and a good work-life balance has a positive and significant influence on employee performance. This study has important implications for the management of the Regional Office of Customs and Excise in formulating policies that support the productive use of social media and facilitate employee work-life balance, thereby improving work quality and productivity.